V Aortic Arch Remnant - Corrado Tagliati; Marco Fogante; Stefania Lamja; Cecilia Cerimele; Alessia Quaranta; Alfonso Alberto Matarrese; Davide Battista; Antonio Bernardini; Giulio Argalia; Iacopo Carbone; Ernesto Di Cesare; Nicolò Schicchi; et al. (Diagnostics)
Here, we describe the case of an asymptomatic 70-year-old male patient who performed a contrast-enhanced computed tomography examination for prostate cancer staging, and an exceptional finding was reported. Specifically, a probable and never before reported minimal V aortic arch remnant with a thin intima–media band that joins together the anterior and posterior aortic walls.